Public Expenditure Policy and the Environment : A Review and Synthesis - Miranda, Kenneth M. (IMF Working Papers; Working Paper ;, 1993)
Commonly cited environmental instruments in the legal, regulatory, and fiscal domains are intended primarily to address market failures to ensure that environmental degradation and resource use is contained to appropriate levels. However, in many instances, environmental degradation is rooted not in market failure, but rather in policy failure. This paper identifies areas of public expenditure policy that interact with the environment. It argues that a reform of certain types of subsidies, increased operations and maintenance expenditures, and a thorough environmental assessment of capital projects will tend to benefit the environment, thereby moving an economy towards 'sustainable' development.